A three-dimensional finite-strain phenomenological model for shape-memory polymers: Formulation, numerical simulations, and comparison with experimental data. (August 2016) - Boatti, Elisa; Scalet, Giulia; Auricchio, Ferdinando
Abstract: Shape-memory polymers (SMPs) represent a class of smart materials able to store a temporary shape and to recover the original shape upon an external stimulus, such as temperature. The present paper proposes a three-dimensional finite-strain phenomenological model for thermo-responsive SMPs, which distinguishes between two material phases presenting different properties and is based on a rule of mixtures. The proposed model is motivated by the earlier work of Reese et al. (2010) and it considers several significant material features that had not been addressed in previous phenomenological approaches. Specifically, the model reproduces both heating-stretching-cooling and cold drawing shape-fixing procedures and it takes into account the non-ideal behavior of realistic SMPs (i.e. imperfect shape-fixing and incomplete shape-recovery). Several numerical tests are reported to assess model performances, from simple uniaxial and biaxial tests to complex simulations of biomedical devices. Comparisons with experimental data taken from the literature are also provided to validate the model. The proposed improvements increase the model applicability over a wide range of polymer types and operating conditions. Highlights: A 3D finite-strain phenomenological model for shape-memory polymers is proposed. The model can reproduce the fundamental behavior of shape memory polymers. The model is able to describe the non-ideal features of real shape memory polymers. FEA simulations are performed to assess model performance and the related algorithm. Compared to experimental data, the numerical curves show a good overall agreement.